PHA-induced inflammation is not energetically costly in the subterranean rodent Ctenomys talarum (tuco-tucos) - Merlo, Julieta (2014)
Immune activity has been proposed to be associated with substantial costs, due to trade-offs with other functions or activities that share common resources and contribute to an animal's fitness. However, direct estimates of the cost of mounting an immune response are few and have been performed mainly in birds. Thus, further work is needed to clarify the relative costs of different components of the immune system and the role of environmental and life-history traits in modulating the costs of resistance. Within the components of immunity, inflammation is considered to be associated with a larger energetic expenditure. Here, we evaluated the energetic cost of the inflammatory response to phytohemagglutinin (PHA) in a wild population of a subterranean rodent, Ctenomys talarum, and the trade-offs between immune activity and reproduction. C. talarum develops an inflammatory response to PHA, but contrary to our predictions, this response was not associated with an increase in oxygen consumption regardless of reproductive status or sex. Our study shows that an immune challenge may not always result in a detectable energetic cost. We discuss the possibility that other currencies could be underlying the cost, such as micro-or macronutrients requirements, autoimmunity or oxidative stress.